Meningkatkan Keterampilan Komunikasi Anak Dengan Metode Bermain Peran Pada Anak Panti Asuhan Mercy Clement Indonesia - Srinita Br Sembiring Milala; Malida Putri (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Communication skills are the main skills that must be possessed by everyone in order to be able to build healthy relationships with anyone and anywhere we are. However, communication skills will be difficult to improve if they are not trained with the right methods, especially for children. Therefore, the author uses the role-playing method to improve the communication skills of one of the children at the Mercy Clement Indonesia Orphanage. In general, the role-playing method is a form of educational game that aims to make someone appreciate and feel the way of thinking of others. This study aims to see how the implementation of the role-playing method in improving communication skills, and the impact of using this method on 10-year-old orphans. Based on the results of data analysis, the role playing method in this study can be used as a solution in solving children's communication problems. The research findings show that the role playing method is very effective in improving the communication skills of orphans at Mercy Clement Orphanage.